160 Turning a crisis into an opportunity for general practice teams in NI. (16th November 2020) - Sands, Louise; Corry, Maura; McEntee, Siobhan; Mason, Ursula; Stirling, Patrick
Abstract : The emergence of COVID-19 saw a seismic change in General Practice with significant clinical, operational and educational challenges across the whole of the primary care team. Information and guidance from multiple different sources emerged at an overwhelming pace for practitioners. There was no robust way of cascading critical information to individuals. Shielded, remote and sessional health care professionals in particular lacked access to sensitive Health and Social Care Board (HSCB) information. It was evident that there was a need for a centralised information platform for professionals. This would provide easily accessible, accurate and up to date information on service changes, operational and clinical guidance as well as legislative changes An MDT working group, with representatives from all professions including trainees was formed to design a central knowledge repository for the whole primary care team. This ensured all practitioners had access to the latest information, equipping them to deliver high quality care during the pandemic. From concept to website launch took just three weeks, with a live web-based educational programme starting just one week later and acting as a catalyst for enhanced primary and secondary care understanding and communication. There are over 150 attendees at weekly live ZOOM educational events, with the programme reflecting learning needs across the whole primary care team Website analytics confirm 'Pageviews' >100, 000 and 'users' >7, 500 and rising with a global audience. A crisis can bring exciting opportunities and a highly effective team can be created from conception in less than 4 weeks with a shared vision, enthusiasm and determination to make it work. Collaborative learning between GPs, fledgling MDTs, and across the primary-secondary care interface has united colleagues around a shared purpose, starting solution-focused conversations.